Community Empowerment in Environmental Health Education, OHS and Balanced Nutrition in Rural Areas - Inna Noor Inayati; Yoanita Hijriyati (Sustainable Applied Modification Evidence Community (SAMEC), 2024)
Community empowerment is one of the main strategies in addressing the challenges faced by rural communities. However, rural empowerment efforts are often faced with various barriers, including low health literacy, dependence on external assistance, and lack of sustainable policy support. This study aims to explore the potential and constraints of community empowerment in environmental health education, occupational safety and health (OSH), and balanced nutrition in rural areas. Data collection was conducted through in-depth interviews with community leaders, health workers, and village government, as well as focus group discussions with local communities. In addition, field observations were made to identify environmental conditions, community behaviours, and practices related to environmental health, OSH, and nutrition consumption patterns. The results of the research will be analysed using a thematic approach to identify patterns and relationships between community participation and the success of empowerment programmes. The findings suggest that community empowerment supported by participatory approaches, local needs-based education, and inter-sectoral synergies can be an effective strategy to address environmental health and OSH issues, and realise the sustainability of community development programmes.